A Review of The Anti-diabetic Activity of Andrographis paniculata (Burm. f.) Nees based in-vivo Study - Titi Komalasari; Sabtanti Harimurti (Intelektual Pustaka Media Utama, 2015)
Diabetes mellitus (DM) is ricing nowadays. DM is a metabolic deasease characterized by increasing of glucose blood level for prolonged time. Patient with DM must take medicine for lowering glucose levels in whole life. Synthetic anti-diabetic agent is commonly used and significantly able to maintain the glucose blood levels. However, many side effects will occur during the treatment. Further, people is trying to find an alternative medicine for DM treatment. This paper will discuss about an alternative medicine for anti-diabetic agent that is called Andrographis paniculata (Burm. f.) Nees based in-vivo study. Search data obtained from PubMed, PMC (PubMed Central), International Food and Research Journal, and Google search engine. Inclution and exclution criteria were used for selection of journals. Inclution criteria were taken is in-vivo study of Andrographis paniculata as anti-diabetic, published in 2000-2014, and free full text journal or PubReader (full text journal in PubMed Central) in English or Indonesian language. Base on reviewed journals that was conducted, anti-diabetic agent of Andrographis paniculata was found in extract, in fractional coumpund (i.e. andrographolide or its analogue AL-1: andrographolide-lipoic acid), and in combination with synthetic drug or other herbal. Therefore, Andrographis paniculata is potentially developed as an alternative anti-diabetic agent.